Screening of virus inhibitory chemicals and neem products against okra yellow vein mosaic virus - and R. JEYARAJAN, K.B. PUN, SABITHA DORAISWAMY (Indian Phytopathology, 2002)
Pot experiments were conducted in the glasshouse to determine the effect of virus inhibitory chemicals (acetyl salicylic acid @ 200 and 500 ppm, salicylic acid @ 500 ppm, benzoic acid @ 500 ppm and barium chloride @ 1000 ppm) and neem products (neemoil @ 3% aqueous solution and neem seed kernel extract @ 5% aqueous solution) on the control of okra yellow vein mosaic virus (OYVMV) infection of okra (cv. Pusa Sawani). The treatments were applied as sprays on the primary leaves of 7-day-old seedlings24 hr before inoculation of the seedlings with viruliferous Bemisia tabaci adults. All the chemicals and neem products significantly reduced OYVMV infection. Among the chemicals, barium chloride was the most effective (76.67% reduction in infection in comparison with the control) followed by acetyl salicylic acid @ 200 ppm and salicylic acid @ 500 ppm, which gave reductions of 75.0 and 73.3%, respectively. Neem oil and neem seed kernel extract reduced virus infection by 88.3 and 86.7%, respectively.